(untitled) (Applied Biological Research, 2019)
Baker’s yeast is used as a leavening agent in bread baking as it converts simple fermentable sugars in dough to CO2 and ethanol. Fermentation by yeast leads to the expansion of dough, its maturation and development of characteristic flavours in cereal-based products. Different strains of yeasts like Saccharomyces cerevisiae, S. exiguous, S. boulardii, etc. are widely used in nourishment and pharmaceutical industry. Yeast is a source of vitamin B, minerals, β-glucan fiber and protein and is used as health supplement. As probiotic, it plays a vital role in folate biofortification, detoxification and bioavailability of nutrients. Anti-cholesterolemic, anti-mutagenic, anti-oxidative and anti-tumuor potential of S. cerevisiae is currently under investigation. Yeast is exploited in several industrial processes including bioethanol production and bioremediation and is an excellent tool for biotechnological applications. This paper reviews the work done on baker’s yeast and its industrial application and health benefits.